Betting on quality indicators to improve inflammatory bowel disease surveillance outcome: All‐in or one to pick?. Issue 4 (9th January 2020) - Sinonquel, Pieter; Bossuyt, Peter; Vermeire, Séverine; Bisschops, Raf
Abstract : This Editorial refers to the article by Smith et al., p 592–599 of this issue .